Doing a research project in sport performance analysis - O'Donoghue, Peter; Holmes, Lucy (Teacher in performance analysis); Robinson, Gemma (Routledge studies in sports performance analysis, 2018)
The research project or dissertation is a core component of any degree programme in the rapidly developing discipline of sport performance analysis. This highly practical and accessible book provides a complete step-by-step guide to doing a research project. Showcasing the very latest research methods, it covers the whole research process, from identifying a research question and system development to data collection, data analysis and writing up the results. Introducing the fundamentals of project planning and management, this book highlights the importance of research ethics and explains the differences between successful undergraduate and postgraduate projects. Full of expert advice and original insights that can be applied to theoretical and empirical research projects, it covers all the key aspects of conducting a degree-level research project, including selecting a research topic and writing a research proposal, working with a supervisor, understanding research ethics, implementing best practices for project management, collecting, interpreting and presenting results.